2022
DOI: 10.1007/s10508-022-02310-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Levels of Social Engagement with Gay Men Is Associated with HIV Related Outcomes and Behaviors: Trends in Australian Behavioral Surveillance 1998–2020

Abstract: Changes to how gay, bisexual, and other men who have sex with men (GBM) connect with each other and with their communities have implications for HIV prevention. Social engagement with gay men (defined as having friends who are gay men and spending time with them) has been associated with HIV related outcomes over time among Australian GBM. Using data collected in national, repeated, cross-sectional surveys of GBM between 1998 and 2020 (N = 161,117), analyses of trends in the prevalence of gay social engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Those who were more socially engaged with gay men and who lived in areas with high concentrations of gay men were more likely to test frequently or receive an STI diagnosis. These results are consistent with previous evidence showing that connection to gay community has been linked to protective sexual health behaviors, such as HIV testing and PrEP use, 17,31 as well as behaviors that increase STI risk such as having a higher number of sexual partners and condomless anal intercourse 24,32 . Our results showed that those who are most sexually active are indeed more likely to engage with STI testing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Those who were more socially engaged with gay men and who lived in areas with high concentrations of gay men were more likely to test frequently or receive an STI diagnosis. These results are consistent with previous evidence showing that connection to gay community has been linked to protective sexual health behaviors, such as HIV testing and PrEP use, 17,31 as well as behaviors that increase STI risk such as having a higher number of sexual partners and condomless anal intercourse 24,32 . Our results showed that those who are most sexually active are indeed more likely to engage with STI testing.…”
Section: Discussionsupporting
confidence: 92%
“…Sexually Transmitted Diseases • Volume 50, Number 12, December 2023 use, 17,31 as well as behaviors that increase STI risk such as having a higher number of sexual partners and condomless anal intercourse. 24,32 Our results showed that those who are most sexually active are indeed more likely to engage with STI testing. Our results demonstrated that substantial proportion GBM are not testing at our lower threshold of ≥3 tests per year compared with the quarterly testing guidelines.…”
Section: Stis In Gay and Bisexual Men In Australiamentioning
confidence: 64%
See 2 more Smart Citations
“…This is also supported by work from Oda et al (2011), showing that social connection (via social support) increases prosocial behavior. Thus, although it is unclear how community identity may relate directly to communal sexual altruism among GBM, given the existing work showing the importance of social connection for the activation of motivations for communal altruism (e.g., Brown & Brown, 2006) and for engagement in some HIV prevention behaviors (Chan et al, 2022), this may be a particularly important factor to consider.…”
Section: Introductionmentioning
confidence: 99%